Modern Perl best practices - Conway, Damian, 1964- (O'Reilly Media, 2014)
"A decade after Perl Best Practices was published, tens of thousands of Perl developers continue to read, debate, and adopt most of the recommendations in the book. But, rather than deliver a fixed and eternal set of rules, author Damian Conway wanted to stimulate a mindset of continual re-evaluation of all Perl coding techniques and tools"--Resource description page.